2009
DOI: 10.1038/sj.bjc.6604891
|View full text |Cite
|
Sign up to set email alerts
|

Integrating BRAF/MEK inhibitors into combination therapy for melanoma

Abstract: The discovery of BRAF mutations in melanoma has not yet translated into clinical success, suggesting that BRAF/MEK inhibitors will need to be combined with other agents. In the current review, we discuss other pathways likely to be important for melanoma progression and suggest possible drug combinations for future clinical testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 37 publications
0
65
0
2
Order By: Relevance
“…For example, mTor is a kinase involved in controlling cell proliferation and motility in many cell types, including T cells (65,66). Although, a combined B-Raf and mTor inhibitor therapy was suggested for tumors (67), no direct link between B-Raf and mTor signaling has been reported. We also found that B-Raf interacted with Rictor, a known binding partner of mTor (68).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mTor is a kinase involved in controlling cell proliferation and motility in many cell types, including T cells (65,66). Although, a combined B-Raf and mTor inhibitor therapy was suggested for tumors (67), no direct link between B-Raf and mTor signaling has been reported. We also found that B-Raf interacted with Rictor, a known binding partner of mTor (68).…”
Section: Discussionmentioning
confidence: 99%
“…BRAF-targeting compounds and MEK inhibitors, designed to disrupt the RAF-MEK-ERK pathway have been developed and are currently being tested in clinical trials for treatment of various human cancers (Beeram et al 2005, Gray-Schopfer et al 2007, Haass et al 2008. Several studies have shown that BRAF mutant cancer cells may be susceptible to anti-cancer drugs, such as AZD6244 (used to treat melanoma) (Smalley & Flaherty 2009). Furthermore, Zheng et al (2009) described the relationship between AMPK and the RAF-MEK-ERK signaling pathway in human melanoma cells harboring a BRAF mutation.…”
Section: Discussionmentioning
confidence: 99%
“…To address these issues, combination of BRAF/MAPK-targeted therapy with other signal transduction inhibitors or with conventional chemotherapy has been proposed (9).…”
Section: Introductionmentioning
confidence: 99%